2007
DOI: 10.1017/s1751731107000262
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones in small ruminants: effects of endogenous, environmental and nutritional factors

Abstract: Appropriate thyroid gland function and thyroid hormone activity are considered crucial to sustain the productive performance in domestic animals (growth, milk or hair fibre production). Changes of blood thyroid hormone concentrations are an indirect measure of the changes in thyroid gland activity and circulating thyroid hormones can be considered as indicators of the metabolic and nutritional status of the animals. Thyroid hormones play a pivotal role in the mechanisms permitting the animals to live and breed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
142
2
15

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(184 citation statements)
references
References 141 publications
15
142
2
15
Order By: Relevance
“…These results are consistent with the stress response to undernutrition, so release of cortisol from adrenal cortex may increase associated with decreased plasma insulin concentrations. Previous studies have indicated that long-term maternal undernutrition in sheep influences both maternal and fetal plasma free T3 and T4 hormone concentrations (Rae et al, 2002;Todini, 2007). However, maternal nutrition intake during periconception period did not alter both maternal and fetal T3 and T4 concentrations in the present study.…”
Section: Figurecontrasting
confidence: 75%
“…These results are consistent with the stress response to undernutrition, so release of cortisol from adrenal cortex may increase associated with decreased plasma insulin concentrations. Previous studies have indicated that long-term maternal undernutrition in sheep influences both maternal and fetal plasma free T3 and T4 hormone concentrations (Rae et al, 2002;Todini, 2007). However, maternal nutrition intake during periconception period did not alter both maternal and fetal T3 and T4 concentrations in the present study.…”
Section: Figurecontrasting
confidence: 75%
“…The primary function of thyroid hormones is to increase metabolic rate in order to maintain a relatively constant body temperature. When the AT increases, serum levels of thyroid hormones decrease and vice versa (Todini 2007). Thus, suggesting that as seasons change, breeds that can effectively regulate thyroid hormone secretion may survive better, particularly in the tropical countries where animals are not be provided with special housing according to the prevailing season of the year.…”
Section: Thyroid Hormonesmentioning
confidence: 99%
“…These hormones have important effects on cell proliferation, differentiation, and migration as well as growth and metabolism of embryos (Krees et al, 2009). They are also important in normal reproduction, productive performance such as growth, milk and hair fibre production in domestic animals and hence affect farm animal productivity (Tondini, 2007). The thyroid also produces calcitonin from the parafollicular cells that regulates calcium metabolism.…”
Section: Introductionmentioning
confidence: 99%